Persistent reversed end diastolic flow in the fetal middle cerebral artery: an ominous finding. (August 2015) - Brownfoot, FC; Cluver, CA; Walker, SP
Fetal persistent middle cerebral artery reversed end diastolic flow is a rare and ominous finding. Previous cases have been associated with intracranial hemorrhage, growth restriction, anaemia, and hepatic anomaly. Intrauterine demise or early neonatal death is a common outcome. We report the case of persistent middle cerebral artery reversed end diastolic flow in a well-grown fetus at 32 weeks' gestation resulting from acute, severe anaemia due to a large feto-maternal hemorrhage. An emergency cesarean section was performed and the neonate required advanced resuscitation and immediate blood transfusion. Postnatal magnetic resonance imaging confirmed a hemorrhagic parietal infarct and bilateral ischaemic changes in the basal ganglia. This provides further evidence that persistent middle cerebral artery reversed end diastolic flow in any fetus is an ominous finding warranting urgent diagnostic evaluation and/or delivery.